Optimization Of Product Diversification and Product Quality Through Digital Sewing Machine Technology and Copper Wax Melting Vats for Batik Craftsmen in Tanjung Bumi - Liosten Rianna Roosida Ully; Muhammad Syahrul Borman; Safrin Zuraidah; Ichlas Wahid (Unram Journal of Community Service, 2025)
Community Empowerment for Regional Superior Products (PM-UPUD), with the title "Improving the Quality, Capacity, and Competitiveness of Green Economy-Based Hand-Drawn Batik Products in Bangkalan Regency," with target partner 1 being Zulpah Batik and target partner 2 being Naraya Batik, operates in the hand-drawn batik, gentongan hand-drawn batik, and uniform industries.The purpose of the PM-UPUD Program is to improve the quality, production capacity, and competitiveness of target partner products so they can compete in both domestic and foreign markets. The problems faced by target partners 1 and 2 are that the number of product variations produced is still limited, they are not keeping up with current fashion trends without abandoning the characteristics of batik, and the production system for making finished clothes and applying malam is still conventional, resulting in low product quality. The solution to solve the partners' problems is the implementation of innovative digital sewing machine technology and a copper wax bath. The methods used to implement the proposed solution are training, mentoring, and practical operation and maintenance of digital sewing machines and copper wax baths. The PM-UPUD achievement target shows an increase in the number of batik fabric diversification products, namely fashion clothing, party suits, and home interior accessories made from batik. There is an increase in production capacity of 25 hand-written batik pieces per day and an increase in sales volume of 35 pieces per day. The external outputs of PM-UPUD are articles in Sinta 4 community service journals, videos, publications in mass media, posters, and the Unitomo YouTube channel. Thank you to the DPPM KEMDIKTISAINTEK for funding this PM-UPUD program in the 2025 fiscal year.